Deposition and Surface Modification of Low-k Thin Films For ILD Application In ULSI Circuits - Y.S. Mhaisagar; B.N. Joshi; A.M. Mahajan (Журнал нано- та електронної фізики)
The low-k thin films have been deposited successfully by sol gel technique using tetraethylorthosilicate (TEOS) precursor and the surface of deposited thin films have been modified by wet chemical treatment using trimethylcholorsilane (TMCS) and hexane solution with 15 % volume ratio to remove the hydroxyl groups from the surface of deposited low-k thin films. The characterization of the as deposited and surface modified low-k thin films has been carried out by Ellipsometer, Fourier transform infrared (FTIR) spectrometer, and contact angle meter. For the determination of the dielectric constant of the deposited thin film the metal –insulator-semiconductor (MIS) structure was formed by depositing the Aluminium (Al) metal on the low-k thin film. Further the capacitance-voltage curve of the MIS structure has been obtained at 1 MHz frequency. The dielectric constant of the as deposited thin film is found to be 2.15. The lowering of O-H peaks and appearance of CH3 peaks in FTIR spectra confirms the surface modification of SiO2 films. The contact angle of the deposited thin film is changed from 83.3° to 104° after surface modification that validates the transformation of thin film surface from hydrophilic to hydrophobic after the surface modification treatment.